Regulação de custos de distribuição de energia elétrica: uma análise comparativa das abordagens de benchmarking utilizadas em países europeus e latino-americanos - Roberto de Barros Mesquita (2017)
Regulatory action seeks to induce productive efficiency gains and improvement of the quality of public utility services in order to reduce costs of regulated firms and, consequently, tariffs practiced, considering the existence of asymmetric information and opportunism. Effectiveregulatory procedures involve incentive mechanisms to regulated companies accurately report cost and demand information, so that optimal prices and results can be determined. Incentive Regulation is increasingly using some form of benchmarking to estimate efficient costs that enable price or revenue adjustments of utilities worldwide without compromising the economic sustainability of companies. In this context, this thesis analyses comparatively processes of regulating electric energy distribution tariffs adopted by European and Latin Americanregulatory agencies in order to identify convergences and divergences about the regulatory strategies used, the main characteristics of efficient costing benchmarking, methodologies and models used, trajectories of reduction of possible inefficiencies and calculation of productivitygains, among others. The study follows a qualitative approach with multiple case studies. The collection of information occurred through technical visits with interviews and/or documentary research with ten European regulators and eight Latin American ones. The results indicate the main convergences found in European and Latin American regulations are related to the regulatory strategy, the duration of the regulatory period, the use of mean values rather than panel data, total costs as the main input of the models, the explanatory variables, the failure to consider environmental variables in the efficient cost estimating models and the absence of a specific standard to define the final efficiency score of companies. The main divergences between European and Latin American regulators are related to the methodologies adopted, the establishment of specific targets to reduce inneficiencies, the definition of general goals of productivity gain and to the consideration of bonus/malus associated to the quality of service in the calculation of allowed revenue of energy distributors. In Brazil, the regulatory agentemploys some specific mechanisms not practiced in other countries surveyed.